Anti-Wear Effect of Graphene Oxide in Lubrication by Fluorine-Containing Ionic Liquid for Steel - Hiroshi Kinoshita (Japanese Society of Tribologists, 2015)
Although fluorine-containing ionic liquids have excellent lubricity as liquid lubricants for steels, strong tribochemical reactions leading to severe wear are occurred during friction. Recently, it is reported that graphene oxide (GO) dispersed in water and oils exhibit good anti-wear property. In this study, in order to investigate anti-wear effect of GO in lubrication of fluorine-containing ionic liquids for steel, tribological properties of mixtures of GO with concentrations of 0.2, 2, and 10 mass% and an ionic liquid ([BMIM][BF4]) were investigated on a steel surface. Under the pure ionic liquid lubrication, a strong tribochemical reaction occurred, resulting in corrosion wear. Under a GO–ionic liquid mixture lubrication with 0.2 mass% GO, wear was much lower than for the pure ionic liquid lubrication. Adding GO would inhibit the strong tribochemical reaction. However, wear was high with the 10 mass% GO–ionic liquid mixture. The GO–ionic liquid mixtures did not greatly decrease the friction coefficient.